Nuclear receptors in metabolism and diseases: Mechanistic and therapeutic insights - Chen-Ying Zhu; Pei-Han Yu; Qi Sun; De-Fei Hong; Chang Yang; Hua Naranmandura (Pharmacological Research)
Nuclear receptors (NRs) are ligand-activated transcription factors that function as metabolic sensors, integrating endogenous and xenobiotic signals to regulate gene networks controlling metabolism, immunity, and cellular homeostasis. Recent studies elucidated the pivotal roles of NRs (e.g., PPARs, LXRs, FXRs, ERs) in metabolic disorders (obesity, diabetes, metabolic dysfunction-associated steatotic liver disease) and certain cancer initiation/progression, particularly through their regulation of lipid metabolism, glucose homeostasis, and cholesterol balance. Fortunately, their activity involves the spatiotemporal dynamic coregulator interactions and pathway crosstalk also provide potential novel targets for therapeutic intervention. Although current drugs still face challenges in achieving tissue specificity and ligand selectivity for nuclear receptors, emerging approaches such as selective nuclear receptor modulators (SNRMs) and proteolysis-targeting chimeras (PROTACs) hold significant promise for treating metabolic and neoplastic disorders. In this review, we systematically summarize their precise regulation of lipid metabolism, glucose homeostasis, and cholesterol balance, which significantly influence disease pathogenesis and development. Additionally, future investigations employing integrated multi-omics approaches, advanced structural biology techniques, and AI-driven analyses will further unravel their precise regulatory mechanisms, paving the way for personalized therapeutic interventions, while critically evaluating their translational potential and clinical applications.